Relative Strength of Common Fixed Point Results for Two Self Mapping in Fuzzy Metric Space - Tiwari, Surendra Kumar; Agrawal, Ranu (Mikailalsys Journal of Mathematics and Statistics, 2025)
The concept of fuzzy metric space, which was introduced by Kramosil and Michalek (1975), is used in this article. In this manuscript, we present and generalize some common fixed point theorems in fuzzy metric spaces, which is an extension of the well-known results given by shen, Y. et al. (2012) in the sense of Schweizer and Sklar(1983).